Edukasi adaptasi kebiasaan baru anak usia sekolah dasar di Desa Sukalaksana: Strategi pencegahan COVID-19 - Risa Susanti; Desti Khoirunnisa R; Frieta Afriantie N; Frida Melinda D. F; Qori Putri A (Jurnal Dedikasi Masyarakat, 2021)
The COVID-19 pandemic has forced society to adapt to new biases to stop the spread of the virus. The purpose of this service is to provide education and support the implementation of Adaptation of New Beliefs (AKB) in the Early Childhood Education Program at Sukalaksana Elementary School, Garut. The implementation methodology includes case studies, interviews, AKB education, and follow-up on IMR implementation for three days after counseling. During lectures, material is delivered using brochures and video material that discusses COVID-19 and the stages of its implementation. In addition, each learning shift is divided into small groups to emphasize compliance with health protocols. Evaluation findings suggest that children's understanding of COVID-19 and IMR practices should be improved. After completing the training, they started practicing AKB techniques such as cleaning their teeth with soap and using masks. This program emphasizes the importance of collaboration between higher education organizations and government.